Evaluation of functional properties of potential probiotic isolates from fermented brine pickle. (1st May 2020) - Ragul, Kessavane; Kandasamy, Sujatha; Devi, Palanisamy Bruntha; Shetty, Prathapkumar Halady
Highlights: Functional properties of Bacillus spp . from fermented mango pickle were studied. Intact cells, intracellular extracts of isolates showed strong antioxidant activity. Isolates showed inhibitory activities towards α-amylase, α-glucosidase, tyrosinase. Bacillus licheniformis displayed strong anticancer activity against HT-29 cell line. Abstract: Fermented foods have been consumed for centuries in various parts of the world and are known to be rich resources of functionally important microorganisms. This study documents the antioxidative, anticancer and enzyme-inhibiting properties of potential probiotic Bacillus strains isolated from fermented brine mango pickle. Antioxidant activity was determined through in-vitro assays namely, DPPH, ABTS +, hydroxyl radical scavenging ability, reducing activity, superoxide anion scavenging ability, linoleic acid and plasma lipid peroxidation ability. Both intact cells (IC) and intracellular cell-free extracts (CFE) from most of the strains exhibited prominent antioxidant activity. Likewise, CFE and intracellular cell-free supernatants (CFS) exhibited potential inhibitory activities towards α-amylase, α-glucosidase and tyrosinase. Interestingly, CFS and crude ethyl acetate extracts of PUFSTP35 ( Bacillus licheniformis KT921419) displayed strong anticancer activity against HT-29 colon cancer cell line. Hence, these probiotic strains have been showed to exhibit unique functional properties and could be further commercially exploited.